Exploring a water data, evidence, and governance theory - Zogheib,C; Ochoa-Tocachi,BF; Paul,JD; Hannah,DM; Clark,J; Buytaert,W (Water Security, 2018)
The hydrological evidence on which water resource management and broader governance decisions are based is often very limited. This issue is especially pronounced in lower- and middle-income countries, where not only data are scarce but where pressure on water resources is often already very high and increasing. Historically, several governance theories have been put forward to examine water resource management. One of the more influential is Elinor Ostrom’s theory of common-pool resources. However while used very widely, the underlying principles of Ostrom’s approach make pronounced implicit assumptions about the role of data and evidence in common-pool resource systems. We argue here this overlooks how power relations, user characteristics, system arrangements, and technological advances modulate fundamental associations between data, evidence, and governance, which we contend need to be considered explicitly. Examining the case of water allocations in Quito, Ecuador, we develop a set of concrete criteria to inform the ways in which Ostrom’s principles can be applied in a data-scarce, institutionally complex, polycentric context. By highlighting the variable impact of data availability on subsequent evidence generation, these criteria have the potential to test the applicability of common assumptions about how to achieve water security in a developmental context, and hence offer the possibility of developing a more encompassing theory about the interactions between water data, evidence, and governance.